Computer Safety, Reliability, and Security SAFECOMP 2012 Workshops: Sassur, ASCoMS, DESEC4LCCI, ERCIM/EWICS, IWDE, Magdeburg, Germany, September 25-28, 2012, Proceedings - Ortmeier, Frank; Daniel, Peter (Programming and Software Engineering, 2012)
This book constitutes the refereed proceedings of 5 workshops colocated with SAFECOMP 2012, the 31st International Conference on Computer Safety, Reliability, and Security, held in Magdeburg, Germany, in September 2012. The 49 revised full papers presented were carefully reviewed and selected from numerous submissions. According to the workshops covered, the papers are organized in topical sections on: next generation of system assurance approaches for safety-critical systems (Sassur), architecting safety in collaborative mobile systems (ASCoMS), dependable and secure computing for large-scale complex critical infrastructures (DESEC4LCCI), ERCIM/EWICS/cyberphysical systems (ERCIM/EWICS), and on digital engineering (IWDE).